2019
DOI: 10.1038/s41598-019-46377-4
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Prescribed Fires Can Reduce Risk of Tick-borne Diseases

Abstract: Recently, a two-year study found that long-term prescribed fire significantly reduced tick abundance at sites with varying burn regimes (burned surrounded by burned areas [BB], burned surrounded by unburned areas [BUB], and unburned surrounded by burned areas [UBB]). In the current study, these ticks were tested for pathogens to more directly investigate the impacts of long-term prescribed burning on human disease risk. A total of 5,103 ticks (4,607 Amblyomma americanum , 76 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 59 publications
1
36
0
Order By: Relevance
“…These issues could be countered by more frequent, longer, and larger scale burns, which correlates with other studies that also believe that burns at higher intensity are most effective in countering ticks than those at low intensity [8]. Gleim et al [10] found that long term prescribed fire (regular burning for 10+ years) significantly reduced tick abundance, regardless of burn interval, host abundance, or vegetation structure. This is primarily due to the change in vegetation structure, creating a hotter and drier environment that is less appealing for ticks [20].…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…These issues could be countered by more frequent, longer, and larger scale burns, which correlates with other studies that also believe that burns at higher intensity are most effective in countering ticks than those at low intensity [8]. Gleim et al [10] found that long term prescribed fire (regular burning for 10+ years) significantly reduced tick abundance, regardless of burn interval, host abundance, or vegetation structure. This is primarily due to the change in vegetation structure, creating a hotter and drier environment that is less appealing for ticks [20].…”
Section: Introductionsupporting
confidence: 66%
“…Reports of overall tick-borne diseases doubled from 2006 to 2018 [3] while the incidence of Lyme disease in the United States has been steadily increasing, from a little less than four cases per 100,000 people in the 1990s to close to 10 cases per 100,000 people in the early 2000s [21]. New pathogens continue to emerge, including heartland virus, Bourbon virus, Borrelia miyamotoi, Borrelia mayonii , and Ehrlichia muris eauclairensis [10]. Climate change has expanded the northern borders of tick habitats and increased winter tick activity, contributing to the prevalence of tick-borne diseases [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, fire on Long Island, New York resulted in halved tick density, but there was no change in the risk of Lyme disease as measured by the density of infected nymphs (Mather et al 1993). In Florida and Georgia, prevalence of tick-borne pathogens in ticks tended not to change despite ongoing prescribed burns, but the overall risk was considered to be lower because of lower numbers of ticks (Gleim et al 2019). Our data suggest a similar increase within one to two years in some small mammal and tick species at high-intensity fire sites.…”
Section: Discussionmentioning
confidence: 99%
“…Fire has been intentionally used for the management of ticks, with evidence that prescribed fire can reduce tick and/or host abundance (Padgett et al 2009, Gleim et al 2019), typically by reducing understory vegetation and litter which provides harborage, food, and questing sites for ticks and their hosts (Lee and Tietje 2005, Padgett et al 2009, Gilliam et al 2018). However, the effectiveness of fire for tick management is inconsistent, in part because prescribed burns tend to be of low intensity and patchy, such that refugia may remain in which ticks and mammalian hosts can persevere (Padgett et al 2009, Pastro et al 2011, Gilliam et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Forests provide a variety of ecosystem services, from carbon sequestration and maintenance of biodiversity to recreation and wood products (Oswalt and Smith 2014). There also is growing evidence that healthy forests buffer transmission of vector-borne infectious diseases and that active forest management, such as invasive plant removal (Williams et al 2009;Gardner et al 2017) and prescribed burns (Padgett et al 2009;Scasta 2015;Gleim et al 2019), may inhibit vector occurrence and disease transmission. In North America, the most epidemiologically significant zoonotic diseases include multiple pathogens transmitted by the blacklegged tick (Ixodes scapularis).…”
Section: Introduction and Purposementioning
confidence: 99%